THE EFFECT OF NET PROFIT MARGIN, CURRENT RATIO, FIRM SIZE, BUSINESS RISK ON CAPITAL STRUCTURE - Anzella Anzella; Cindy Audryana; Esmeralda Esmeralda; Firmansyah Mida (Berkala Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this study is to examine and analyze the effect of net profit margin, current ratio, firm size, business risk on capital structure in basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. This study uses a quantitative research approach. The type of research used is descriptive quantitative research. The nature of this research is cause and effect/causal research.The population of this study amounted to 67 basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. The number of research samples is 31 basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period with a sample of 124 observations. Data collection technique using documentation and research model is multiple linear regression. The results of this study are that the net profit margin has an effect and is not significant on the capital structure of basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. The current ratio has no significant effect on the capital structure of basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. Firm size has a significant and significant effect on the capital structure of basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. Business risk has an effect and is significant on the capital structure of basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017 period. Net profit margin, current ratio, firm size, business risk have a significant and significant effect on the capital structure of basic and chemical industrial companies on the Indonesia Stock Exchange for the 2014-2017.